Methods and methodologies in Fiqh and Islamic economics - Saleem, Muhammad Yusuf (2008)
This paper intends to examine the methods of reasoning that are employed in Fiqh and critically discuss their adoption in Islamic economics. The paper argues that the methods used in Fiqh are mainly designed to find out whether or not a certain act is permissible or prohibited. Islamic economics, on the other hand, is a social science. Like any other social science its proper unit of analysis is the society itself. Methodologies of Fiqh and Islamic economics also differ as the former focuses on prescriptions. It prescribes what an individual should do or avoid. In contrast, Islamic economics is more concerned with describing economic phenomena. While Fiqh, especially worship (lbadat) type, prescriptions are permanent in nature and for all individuals, economic descriptions may change from time to time and from society to another. This paper argues that the methods of reasoning for discovering the truth in jiqh and Islamic economics are not necessarily identical. While jiqh has a well developed methodology in the form of llsul al-fiqh, Islamic economics in its search for finding the truth should rely on a methodology that suits its social and descriptive nature.